Ideal characteristics of a listening device - Chappel, Alexia (Department of Health and Rehabilitation Sciences, 2025)
Hearing impairment constitutes a significant global health challenge, affecting millions, particularly within the elderly demographic. It is expected that without intervention, the number of individuals with hearing impairment will surge to 630 million by 2030 (WHO, 2018). Despite its adverse effects on well-being, including mental health issues such as depression and anxiety, hearing loss is often insufficiently addressed, resulting in low adoption rates for hearing aids (HAs) (McCormack & Fortnum, 2013). Over-the-counter listening devices (OTCLDs) have emerged as a potential solution to enhance accessibility and affordability, although they are met with professional reservations (Manchaiah et al., 2023). A listening device (LD) is used to improve overall communication of individuals with hearing difficulties as well as enhance speech signals through amplification equipment within the device (Kim & Kim, 2014). Research focusing on patient preferences for HAs underscores the importance of attributes like comfort, feedback reduction, and cost-effectiveness (Bridges et al., 2012). Due to the low utilisation of LDs, there has been growing interest in the users' preferences for LDs and what their ideal LD would consist of in order to promote usage for mild to moderate sensorineural hearing losses (SNHL) (Urbanski Dana et al., 2021). In summary, prioritising the expansion of innovative hearing technologies should be a central policy concern to comprehensively address untreated hearing loss. Aim: The aim was to determine what factors could influence the overall uptake of listening devices (LDs) for future potential users over the age of 18. Objectives: Determine individuals preferred characteristics of LDs. Explore factors that influence uptake of LDs. Determine individuals' views on LDs. Research design: This study employed a mixed-methods approach, incorporating both quantitative and qualitative research methods. Quantitative data were collected through descriptive Likert scale questionnaires (LSQs), while qualitative insights were obtained through descriptive semi- structured interviews (SSIs). Employing a convergent mixed-methods approach was appropriate for the study as it allowed for the exploration and integration of data from various aspects of the methodology (Fetters, Curry, & Creswell, 2013). Data analysis included quantitative methods using descriptive statistics and chi-square tests, as well as qualitative techniques, including content analysis. Methodology: Participant recruitment: Participants were recruited through various social media platforms which include the researcher's personal profile on LinkedIn and Facebook as well as Facebook Community groups. Flyers (Appendix A, B, C & D) were sent out to companies and put-up all- over South Africa (Appendix E) (coffee shops and businesses). Sampling: The study used purposive snowball sampling, selecting participants based on predefined criteria (Taherdoost, 2016). Both research designs employed non-probability sampling, which reduced time and costs (Palys, 2008; Kar & Ramalingam, 2013). Snowball sampling was used for the LSQ, with participants sharing study information and the questionnaire. However, its limitation restricted generalising findings to the broader South African population (Naderifar et al., 2017). This approach intentionally selected individuals with specific characteristics relevant to the study (Creswell, 2014; Etikan, 2016). The estimated sample size was 159 participants for the LSQ, as determined using the G-power calculator, and six to eight participants for the SSIs. Purposive sampling techniques were employed to select participants for the SSIs. Individuals who expressed their willingness to participate were included in the study. The estimated sample size for the SSIs was six to eight participants. Results: A total number of 159 participants took part in the LSQ part of the study and 7 of those participants took part in the SSIs. The study sample was predominantly female, with 70% of participants identifying as such, highlighting a notable predominance of female representation. No participants identified with other sex categories or chose not to disclose their sex, suggesting that all participants were either comfortable sharing this information or did not consider it pertinent to the study. The age distribution of participants is as follows: 34% are 18- 29 years old, 26% are 30-44 years old, 28% are 45-59 years old, and 12% are 60 years or older. This shows a diverse range of ages, with a concentration in younger to middle-aged adults. Data shows a strong preference for rechargeable OTCLDs, with 71% of users choosing this option due to its convenience, environmental benefits, and improved battery technology (Johnson, 2017). Sex significantly influenced recommendations based on positive experiences (X2 (3, N =159) = 3, p = .008), with females more likely to strongly agree and males more likely to agree. Comfort was deemed crucial by participants aged 30-44 (85.7%) and 45-59 (82.6%) compared to those aged 18-29 (60.7%) and 60+ (68.4%) (χ2 = (3, N = 159) = 10.27, p = .016). Older adults (60+) were more likely to endorse training programs for increasing device uptake (χ2 = (9, N = 159) = 18.25, p = .032), but also more likely to disagree about their effectiveness (21.1% vs. 5.4% for ages 18-29). A trend suggested that age impacts perceptions of LD benefits (χ2 = (6, N = 159) = 12.19, p = .058). Males showed a preference for rechargeable devices, and age was associated with valuing comfort, with those aged 30- 59 valuing it more than younger and older participants. The most valued features were cost, comfort, style, and battery life, while noisy/quiet environments and water/sweat resistance were less important. To improve uptake, cost, education, and comfort were highlighted as key factors, while high cost, discomfort, and stigma were identified as barriers. Conclusion: In conclusion, this thesis effectively develops and applies the Likert scale questionnaire (LSQ) to uncover critical factors influencing the adoption of listening devices (LDs). The LSQ highlights that users prioritise comfort, battery life, and connectivity/Bluetooth as essential features, emphasising the need for ergonomically designed devices with extended battery life and reliable connectivity. Supplementary interview data reveal key adoption barriers, with education emerging as the most significant factor, followed by cost, with awareness of hearing impairment and stigma playing lesser roles. By comparing these findings, the research offers a comprehensive view of both the desirable features and challenges faced in LD adoption. For increased usage, it is crucial for manufacturers to focus on enhancing product design and for stakeholders to address educational needs, affordability, and awareness. This integrated approach promises to improve user satisfaction and adoption rates, aiding individuals in overcoming hearing difficulties and enhancing their quality of life.